2012
DOI: 10.1007/978-3-642-34614-9
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Engineering of Embedded Systems

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Through the longtime experience obtained within the research projects SPES [21] and E-Energy 1 , we empirically confirmed the presence and challenges of the above stated limitations for the avionic, automotive, and smart grid domain. Driven from the individual problems recognized in each domain, there is a natural question whether it is possible to extend standard formal methods to allow on the one hand to speed up the development of specifications while on the other hand the specification should remain formal enough to allow the promises of formal methods such as verification, model checking, etc.…”
Section: Introductionsupporting
confidence: 53%
“…Through the longtime experience obtained within the research projects SPES [21] and E-Energy 1 , we empirically confirmed the presence and challenges of the above stated limitations for the avionic, automotive, and smart grid domain. Driven from the individual problems recognized in each domain, there is a natural question whether it is possible to extend standard formal methods to allow on the one hand to speed up the development of specifications while on the other hand the specification should remain formal enough to allow the promises of formal methods such as verification, model checking, etc.…”
Section: Introductionsupporting
confidence: 53%
“…A requirements list is not a static document. It has to be updated, changed and customized during the whole development process (Pohl and Rupp, 2015;Gräßler and Hentze, 2017). Furthermore, in addition to the definition of requirements, the implementation of testability has to be defined in early stages at the left side of the V-model.…”
Section: Continuous Requirements Elicitation and Managementmentioning
confidence: 99%
“…On the one hand, models provide clear structures to deal with the complexity. On the other hand, models are a simple understandable and standardized language for all involved engineers and managers (Pohl et al, 2012;Gräßler et al, 2016;Eigner et al, 2017). Additionally, most mechatronic product development processes are faced with cost and time pressure.…”
Section: Model-based Design Approachmentioning
confidence: 99%
“…both approaches being based on concepts of existing, well-established design approaches from different disciplines. Essential aspects which are used in both the mecPro² Model Framework and the SCM are:  The RFLP approach from the MVPE Model (Eigner et al, 2012(Eigner et al, , 2014a(Eigner et al, , 2014b  The viewpoints of the SPES Modeling Framework (Pohl et al, 2012)  The subdivision in requirement and solution space including the three axes of concretization, decomposition and variation of the Munich Model of Product Concretization (Ponn and Lindemann, 2011;Lindemann, 2014) through the Context Level. The reason for this lies, inter alia, in the consideration of the transformation of natural language requirements into model-based requirements described by SysML elements and their interrelations (Eigner et al, 2015(Eigner et al, , 2016(Eigner et al, , 2017b.…”
Section: Comparisonmentioning
confidence: 99%
“…The reason for this lies, inter alia, in the consideration of the transformation of natural language requirements into model-based requirements described by SysML elements and their interrelations (Eigner et al, 2015(Eigner et al, , 2016(Eigner et al, , 2017b. This concept is used in the SPES Modeling Framework as well (Pohl et al, 2012) and is explained in more detail by Rupp and SOPHIST (2013). The subdivision of the solution space in both models is inspired by the (R)FLP approach from the MVPE Model.…”
Section: Comparisonmentioning
confidence: 99%